Narrative Pedagogy for Spiritual Empowerment: A Typological Figuration of Qaṣaṣ in the Quran - Bin Muhammad Yusoff, Muhammad Fawwaz (Universitas Islam Raden Rahmat Malang, 2023)
The concept of narrative holds a pivotal position in the Qurʾān, yet it has been subject to inadequate scrutiny and insufficient representation in pedagogical discourse concerning Islamic education. The present work aims to address this knowledge gap by utilising the constructivist grounded theory method to examine the Qurʾān and major exegeses. It specifically focuses on analysing the term qaṣaṣ, which conveys the concept of narrative. This paper delves into the profound tracts and maqāṣid (objectives) that qaṣaṣ hold in the Qurʾān and contemplates their exhortation for education on Islam and modern pedagogy. The analysis reveals that the qaṣaṣ present in the Qurʾān serves as a fundamental framework that directs the essence of the narrative pedagogy model of teaching and learning between pedagogue and learner. Through typological figuration, the listener’s contemplation leads to a re-evaluation of conventional notions surrounding the dynamics between pedagogue and learner and the dissemination of narrative within a pedagogical setting. The triad of truth, beauty and explication are fundamental pillars within this Islamic framework for narrative pedagogy, representing the essence of the human condition concerning education. Because these domains emerge from the concept of qaṣaṣ, the integration of the framework into Islamic education is a matter of utmost importance, given its centrality in the Qurʾān to foster and perfect the principles of Muslims and their sense of self.